Adapting English 10 textbook towards promoting learner's autonomy and communicative competence in learning grammar - Nguyễn, Thị Hồng Châm (University of Languages and International Studies, 2017)
Part one: Introduction. Part two: Development (Chapter 1: Literature review. Chapter 2: The study. Chapter 3: Application). Part three: Conclusion.